Pattern and frequency reconfigurable antenna with diode loaded ELC resonator. Issue 2 (31st July 2019) - Singh, Ghanshyam; Kanaujia, Binod K.; Pandey, Vijay K.; Gangwar, Deepak; Kumar, Sachin
Abstract: In this work, a new compact, low profile, frequency, and end-fire pattern reconfigurable antenna is presented. The proposed antenna consists of four parasitic elements and an electric-inductive-capacitive (ELC) resonator enclosed with a closed ring resonator (CRR). The reconfigurability in the proposed antenna is achieved with the help of five PIN diodes (D1–D5) embedded on the top surface of the substrate. The diode (D1) is implanted between ELC and CRR resonators for frequency reconfigurability. The other four diodes (D2–D5) are implanted between the ground plane and four parasitic elements to control the electrical length of the ground plane to achieve pattern diversity. The ground plane and parasitic elements steer the primary omni-directional beam to bi-directional and uni-directional end-fire radiation at multiple frequencies. The proposed antenna exhibits multiband operation and end-fire pattern diversity depending upon the different states of PIN diodes. The overall size of the proposed antenna is 0.20 λ 0 × 0.17 λ 0 × 0.009 λ 0, where λ 0 is calculated at the lowest resonance frequency. The impedance bandwidth of the antenna ranges from 1.45 to 26.22%, while peak gain varies from 0.86 to 3.86 dBi depending upon the state of operation. The measured results are in agreement with the simulated results, which confirm the frequency and pattern diversity performance of the antenna. The proposed antenna can be used in back-to-back repeater systems.